Obtenção e caracterização de vinho e vinagre de manga (Mangifera indica L.): parâmetros cinéticos das fermentações alcoólica e acética - Cosme Damião Barbosa (2014)
The mango is one of the most cultivated tropical fruits. Its pulp is rich in carbohydrates, which make it an excellent raw material for the production of fermented alcoholic beverages. This study aimed to evaluate eight yeast strains for the production of a mango wine and to obtain vinegar using the Orleans method. With this goal, the it was determined the kinetic parameters for alcoholic and acetic fermentation and the produced wine and vinegar were physico-chemically characterized. In the first part of this study, the yeast that showed the best results for the fermentation parameters such as alcohol content, yield and productivity of ethanol was used in the production of mango wine. The fruits used in this study showed pulp yield higher than 70 % with total soluble solids of 17 ° Brix. The mango pulp to fermentation was previously hydrolyzed with enzyme complex Pectinex Ultra SP at a concentration of 0.025 g per kilogram of pulp with enzymatic activity 4000PG. The fermentation to production of mango wine was perfomed in triplicate in plastic containers with a capacity for five liters. Were used as inoculum cells of S.cerevisiae from commercial pressed yeast. The fermentation was conducted in triplicates and cells yeast of S. cerevisiae were used as inoculum was the commercial pressed yeast 3 % (p . v-1 ) on a wet basis. The alcoholic fermentation lasted 48 hours and samples were taken throughout the process. The tumultuous phase lasted for 12 hours. The parameters of the alcoholic fermentation for obtaining the mango wine were: yield close to 7,6 g . L- 1. h -1, efficiency above 91,5 % and yields above 85 %. The wine showed an average alcohol content of 7,6 ( g. L -1). In the second part of the study it was first produced the mango vinegar using the alcoholic fermentation and then acetic fermentation was performed. The wine obtained showed 7.7 Ethanol (g. L -1), ethanol yield of 90 %, efficiency of 96.7 % and yield of 8.03 g. L-1. h-1. The acetic fermentation of mango fermented was performed by slow or "Orleans" process and it was used as inoculum for 100 ml unpasteurised strong vinegar per 1 L of wine. The acetylation was performed in triplicate in plastics containers and conducted for 28 days with samples taken every seven days in order to determinate of volatile acidity in acetic acid, pH and ethanol. Vinegar showed total acidity of 4 g. 100 ml 1 in acetic acid. The volatile acidity was 3.21 in acetic acid being below the required legislation. The yield (GK) of 64 %. The levels of polyphenols were higher when compared with the data from the production other vinegars. Therefore, the yeasts from the commercial pressed yeast showed good results in biotechnological processes tested. The mango wine presented satisfactory values of the physic-chemical parameters analyzed. Thus, It is possible to make mango wine and vinegar of good quality within the parameters required by the legislation and the quality parameters as observed in other scientific articles from the yeast S. cerevisiae from commercial compressed yeast observed in other scientific articles from the yeast S. cerevisiae from commercial compressed yeast.